2013
DOI: 10.1038/hdy.2012.117
|View full text |Cite
|
Sign up to set email alerts
|

Linking transcriptomic and genomic variation to growth in brook charr hybrids (Salvelinus fontinalis, Mitchill)

Abstract: Hybridization can lead to phenotypic differences arising from changes in gene expression patterns or new allele combinations. Variation in gene expression is thought to be controlled by differences in transcription regulation of parental alleles, either through cis-or trans-regulatory elements. A previous study among brook charr hybrids from different populations (Rupert, Laval, and domestic) showing distinct length at age during early life stages also revealed different patterns in transcription regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
(64 reference statements)
1
5
0
Order By: Relevance
“…5 ). Previous studies showed significant associations of their homologous genes with economic traits in animals 42 43 , supporting the notion that these genes could be selected during breeding for genetic improvement. These candidate genes under selection identified in our study could provide useful information for rapidly identifying DNA markers associated with economically important traits in Tilapia.…”
Section: Resultssupporting
confidence: 53%
“…5 ). Previous studies showed significant associations of their homologous genes with economic traits in animals 42 43 , supporting the notion that these genes could be selected during breeding for genetic improvement. These candidate genes under selection identified in our study could provide useful information for rapidly identifying DNA markers associated with economically important traits in Tilapia.…”
Section: Resultssupporting
confidence: 53%
“…report the use of reciprocal hybrids, whereas in this study, hybrid eggs originated only from domesticated animals. Third, since parental effects vary over time, and seem to be most pronounced at the yolk sac resorption stage, and tend to decrease over time, the sampling time-point selected could also have contributed to the gene expression differences of the hybrids [ 73 ]. Indeed, in the current study a higher proportion of genes showed a dominant inheritance pattern at the yolk sac stage (52%) then during exogenous feeding (42%), suggesting stronger maternal influence at the earlier life stage.…”
Section: Resultsmentioning
confidence: 99%
“…Genes were classified as either dominant, underdominant, overdominant, or additive. Following convention ( Gibson et al 2004 ; McManus et al 2010 ; Bougas et al 2013 ; Schaefke et al 2013 ), here dominant, overdominant, and underdominant refer to the mode of inheritance, not selection or fitness. These categories of expression patterns were defined similarly to previous studies ( McManus et al 2010 ; Bell et al 2013 ).…”
Section: Methodsmentioning
confidence: 99%